P53 and cancer-associated sialylated glycans are surrogate markers of cancerization of the bladder associated with Schistosoma haematobium infection. - Júlio Santos; Elisabete Fernandes; José Alexandre Ferreira; Luís Lima; Ana Tavares; Andreia Peixoto; Beatriz Parreira; José Manuel Correia da Costa; Paul J Brindley; Carlos Lopes; Lúcio L Santos (Public Library of Science (PLoS), 2014)
Bladder cancer is a significant health problem in rural areas of Africa and the Middle East where Schistosoma haematobium is prevalent, supporting an association between malignant transformation and infection by this blood fluke. Nevertheless, the molecular mechanisms linking these events are poorly understood. Bladder cancers in infected populations are generally diagnosed at a late stage since there is a lack of non-invasive diagnostic tools, hence enforcing the need for early carcinogenesis markers.Forty-three formalin-fixed paraffin-embedded bladder biopsies of S. haematobium-infected patients, consisting of bladder tumours, tumour adjacent mucosa and pre-malignant/malignant urothelial lesions, were screened for bladder cancer biomarkers. These included the oncoprotein p53, the tumour proliferation rate (Ki-67>17%), cell-surface cancer-associated glycan sialyl-Tn (sTn) and sialyl-Lewisa/x (sLea/sLex), involved in immune escape and metastasis. Bladder tumours of non-S. haematobium etiology and normal urothelium were used as controls. S. haematobium-associated benign/pre-malignant lesions present alterations in p53 and sLex that were also found in bladder tumors. Similar results were observed in non-S. haematobium associated tumours, irrespectively of their histological nature, denoting some common molecular pathways. In addition, most benign/pre-malignant lesions also expressed sLea. However, proliferative phenotypes were more prevalent in lesions adjacent to bladder tumors while sLea was characteristic of sole benign/pre-malignant lesions, suggesting it may be a biomarker of early carcionogenesis associated with the parasite. A correlation was observed between the frequency of the biomarkers in the tumor and adjacent mucosa, with the exception of Ki-67. Most S. haematobium eggs embedded in the urothelium were also positive for sLea and sLex. Reinforcing the pathologic nature of the studied biomarkers, none was observed in the healthy urothelium.This preliminary study suggests that p53 and sialylated glycans are surrogate biomarkers of bladder cancerization associated with S. haematobium, highlighting a missing link between infection and cancer development. Eggs of S. haematobium express sLea and sLex antigens in mimicry of human leukocytes glycosylation, which may play a role in the colonization and disease dissemination. These observations may help the early identification of infected patients at a higher risk of developing bladder cancer and guide the future development of non-invasive diagnostic tests.